2002
DOI: 10.1046/j.1365-2648.2002.02324.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between patients and professionals in the assessment of patient needs: a quantitative study of Norwegian mental health care

Abstract: Sammendrag:Fagfolk og pasienter viste tydelig uenighet med hensyn til mengde og type behov som var til stede. Spesielt fagfolk identifiserte flere behov enn pasienter (9,3 vs. 4,3, henholdsvis) og denne forskjellen var preget av et sterkt faglig fokus på behov angående profesjonell overvåking og oppfølging. En lav faglig vekt på brukermedvirkning kan vaere indisert i noen tilfeller. Resultatene er diskutert med hensyn til spenningen mellom autonomi og omsorgsbehov.Omsorgsbiblioteket har ikke tilgang til å publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
(50 reference statements)
0
18
1
Order By: Relevance
“…Health professionals in several countries have recognized the importance of client participation in program development if they are to become engaged in health promotion and prevention activities and access health care at earlier stages of life-threatening diseases (Hansen, Hatling, Lidal, & Ruud, 2002;Thorne & Patterson, 2000). This study shows that older women in Bangladesh can be engaged in such a planning process, and that they have many creative and viable suggestions about how to increase their access to health services.…”
Section: Discussionmentioning
confidence: 89%
“…Health professionals in several countries have recognized the importance of client participation in program development if they are to become engaged in health promotion and prevention activities and access health care at earlier stages of life-threatening diseases (Hansen, Hatling, Lidal, & Ruud, 2002;Thorne & Patterson, 2000). This study shows that older women in Bangladesh can be engaged in such a planning process, and that they have many creative and viable suggestions about how to increase their access to health services.…”
Section: Discussionmentioning
confidence: 89%
“…For Hansen et al . (), such discrepancies relate to the paternalism of clinicians, while Skinner et al . () noted ‘that patient and professional recall frequently do not concord with one another’ (p. 560).…”
Section: Study Limitationsmentioning
confidence: 99%
“…In addition, we know that service user and provider perspectives on treatment and care are not necessarily the same [13]. For example, studies have found differences in patients' and providers' views on the person's need for monitoring and follow-up from mental health services [14][15][16]. Service users and providers also differ in their views on the perceived barriers to collaborative treatment planning [17].…”
Section: Introductionmentioning
confidence: 99%